The Titanosaur Sauropods from the late Campanian–early Maastrichtian Allen Formation of Salitral Moreno, Río Negro, Argentina - Garcia, Rodolfo Andres (2013)
The dinosaur record of the Salitral Moreno locality (Río Negro Province, Argentina) is characterized by a high diversity of herbivore taxa, among them hadrosaurs, ankylosaurs, and titanosaur sauropods, but carnivores are rare, consisting of only a few fragmentary bones of small forms. Titanosaurs are represented by Rocasaurus muniozi and Aeolosaurus sp., and at least four other taxa, represented by fragmentary material. The elements preserved include a cervical, dorsal and caudal vertebrae, chevron, humerii, ulnae, radii, metacarpal, femora, tibiae, metatarsal, ischia, pubis, and ilium. The Allen Formation is thought to be correlated with the Marília Formation in Brazil, and their faunas have certain elements in common such as aeolosaurines, but saltasaurines and hadrosaurs, are known exclusively from the Allen Formation. These ab− sences, and particularly that of the saltasaurines, may be because those sauropods originated late in the Cretaceous, probably in southern South America (Northern Patagonia?), and they did not have time to disperse to northern South America.